Molecular characteristics of endemic animal viruses: Insights from ecology, evolution, and case studies - Lapian, H.F.N.; Nangoy, M.J.; Laatung, S. (ZOOTEC, 2026)
Endemic animal viruses represent a critical but often underappreciated dimension of global virology and One Health. Persisting within specific wildlife reservoirs, these viruses typically cause little pathology in their natural hosts, yet they harbor molecular traits that enable adaptation, immune evasion, and, under the right ecological circumstances, cross-species transmission. Advances in high-throughput sequencing and molecular characterization have revealed the genomic plasticity, receptor-binding versatility, and immune-modulatory strategies that underpin viral persistence and pathogenic potential. This critical review synthesizes current knowledge of the molecular characteristics of endemic viruses, focusing on three representative families with significant implications for livestock, wildlife, and human health: Orthomyxoviridae (avian influenza viruses in waterfowl), Paramyxoviridae (henipaviruses in bats), and Herpesviridae (malignant catarrhal fever viruses in wild ruminants). We employed a structured literature search to identify key molecular determinants, such as polymerase adaptations, glycoprotein receptor usage, and latency mechanisms, that contribute to ecological fitness and spillover potential. The review integrates these molecular findings with ecological perspectives, emphasizing how factors such as habitat encroachment and wildlife–livestock interfaces amplify risks. By bridging molecular virology with ecology, we advocate for a comprehensive One Health approach to understanding endemic animal viruses. Keywords: Endemic animal viruses; Molecular virology; Paramyxoviridae; Orthomyxoviridae; Herpesviridae.